A better man [large type] - Penny, Louise (Penny, Louise. Three Pines mystery., 2019)
It's Gamache's first day back as head of the homicide department, a job he temporarily shares with his previous second-in-command, Jean-Guy Beauvoir. Flood waters are rising across the province. In the middle of the turmoil a father approaches Gamache, pleading for help in finding his daughter. As crisis piles upon crisis, Gamache tries to hold off the encroaching chaos, and realizes the search for Vivienne Godin should be abandoned. But with a daughter of his own, he finds himself developing a profound, and perhaps unwise, empathy for her distraught father.